Niejednoznaczność wypowiedzi humorystycznych a kompetentne komunikowanie się - Kucharski, Adam (Człowiek i Społeczeństwo, 2020)
The aim of this paper was to discuss competent communication, specifically humorous statements containing ambiguity. Attention was brought to difficulties when deciding between informative and humorous manners of communication. It is not easy to differentiate between the two manners, which means we do not always adjust to the correct manner when speaking with our conversationalist. It brings special difficulties, when the communicator knowingly does not state what manner his speech should be received in. Farther, we cannot always form a phrase in a certain manner, even if the manner is known to us, which can lead to further issues in communication. Communication competency, including humour competency is not only the ability to understand and appreciate the humorous aspect in the message, but also the ability to formulate a humorous statement appropriate for the situation and to the aims raised by an individual.